Elastic buckling and optimization of asymmetric i-cross sections of cold-formed thin-walled beams - Magnucki, K.; Ostwald, M. (Фізико-математичне моделювання та інформаційні технології, 2006)
Subject of the paper includes two open asymmetric I-cross sections of cold-formed thin-walled beams. The both beams are simply supported and are subjects to pure bending. Every I-section is separately described by dimensionless parameters. Geometric properties with warping functions and inertia moments are determined. The strength, global and local stability conditions are defined for both beams. Mathematical solution of elastic local buckling problem for the flange of I-thin-walled beam is experimentally verified. Optimal open cross section shapes of both beams are determined. The optimization criterion is formulated on the basis of a dimensionless objective function. Optimal open cross sections of both beams are compared with a classical I-section beam.